Low-dose computed tomography scan and biopsy for assessing lung cancer prevalence and related factors in high-risk populations - Duy Hoang Tran; Tho Van Nguyen; Linh Thi My Luong; Hoang Minh Phan; To To To; Thuy Thi Cam Bui; Ngoc Thi Minh Nguyen; Phuong Minh Nguyen; Lan Thi Tuyet Le (Heliyon, 2024)
Background: Lung cancer is the second most diagnosed cancer and the leading cause of cancer death in 2020, representing approximately one in 10 (11.4 %) cancers diagnosed and one in 5 (18.0 %) deaths. There are currently very few studies evaluating the prevalence and related factors of lung cancer detected using low-dose CT scans. Objective: Evaluate the prevalence and related factors of lung cancer using low-dose CT scans in high-risk populations in Vietnam. Materials and methods: A cross-sectional analysis study of 169 high-risk patients was conducted to assess the lung cancer prevalence and related factors. Enrolled patients received a physical examination, low-dose computerized tomography scan, and biopsy if abnormalities were found through the CT scan. Univariable and Multivariable analysis through Odd Ratio (OR) to assess the related risk of lung cancer. Results: A total of 169 high-risk patients with a mean age of 62.93 ± 9.31 (years), and the majority were male (91.7 %). Of which 4 cases (2.37 %) were recorded with lung cancer, 3 cases of adenocarcinoma, and 1 case of squamous cell carcinoma. A history of smoking and Chronic Obstructive Pulmonary Disease (COPD) were associated with an increased risk of abnormalities on lung CT scans. Multivariate regression analysis revealed that smoking over 30 pack-years and COPD significantly increased the risk of abnormalities on lung CT scans, p < 0.05.100 % of lung cancer-detected cases were male and smoking ≥30 pack – years. Conclusion: The prevalence of lung cancer in the Vietnamese high-risk population was relatively high. Relative factors such as smoking ≥30 pack - years, and COPD had increased risk of CTscan abnormalities.